Aiming too high: Shoulder injury related to vaccine administration (SIRVA): A case series. Issue 52 (12th December 2022) - Marshall, Tessa; Addison, Mel; Crawford, Nigel W; Buttery, Jim P; Cheng, Daryl R
Abstract: Purpose: Shoulder injury directly related to vaccination (SIRVA) occurs when a vaccine is administered too high in the shoulder. The primary aim of this study was to accurately detail the occurrence, symptoms, diagnosis, management and long-term outcomes of SIRVA cases in Victoria, Australia. Principal results: The study identified 102 SIRVA cases from 2007 to 2020 from the Surveillance of Adverse Events Following Vaccination in the Community (SAEFVIC) database. The majority [73/85; (86 %)] of cases resolved completely with a median time to resolution of 8 weeks and no statistically significant difference in recovery by immunisation provider type or baseline imaging. Major conclusions: This large case series includes long-term clinical progress in SIRVA, allowing accurate evaluation and analysis. Further evaluation is required to establish if other risk factors contribute to SIRVA, which may help with targeted, tailored education for providers on correct vaccine administration technique, including in large and rapid vaccine rollouts.